Residual Inhibition, Hearing Loss and the Neural Basis of Tinnitus - Moffat, Graeme (My University, 2007)
The phenomenon of residual inhibition, whereby the phantom sensation of tinnitus is suppressed following the presentation of a masking stimulus, has significant implications for understanding the neural basis of tinnitus itself. By using novel psychoacoustic techniques and three computer-based tools developed and applied specifically to measure tinnitus sensation and residual inhibition, a pattern emerges in which the depth and duration of tinnitus suppression relates to the center frequency of the band-passed noise masking stimulus. A correspondence between the region of hearing loss, the tinnitus spectrum and the masking stimuli most effective in suppressing tinnitus is revealed. These results suggest that cortical reorganization observed in animal models of tinnitus is not the principal basis of tinnitus, and provide a baseline for optimizing residual inhibition in individual cases and for further experiments.
Residual Inhibition, Hearing Loss and Tinnitus
Keywords: hearing loss; tinnitus; residual inhibition